Bacteriocin Gene-Trait matching across the complete Lactobacillus Pan-genome - Fergus W. J. Collins (Nature Portfolio, 2017)
Abstract Lactobacilli constitute a large genus of Gram-positive lactic acid bacteria which have widespread roles ranging from gut commensals to starters in fermented foods. A combination of in silico and laboratory-based screening allowed us to determine the overall bacteriocin producing potential of representative strains of each species of the genus. The genomes of 175 lactobacilli and 38 associated species were screened for the presence of antimicrobial producing genes and combined with screening for antimicrobial activity against a range of indicators. There also appears to be a link between the strains’ environment and bacteriocin production, with those from the animal and human microbiota encoding over twice as many bacteriocins as those from other sources. Five novel bacteriocins were identified belonging to differing bacteriocin classes, including two-peptide bacteriocins (muricidin and acidocin X) and circular bacteriocins (paracyclicin). In addition, there was a clear clustering of helveticin type bacteriolysins in the Lactobacillus acidophilus group of species. This combined in silico and in vitro approach to screening has demonstrated the true diversity and complexity of bacteriocins across the genus. It also highlights their biological importance in terms of communication and competition between closely related strains in diverse complex microbial environments.